Surgical treatment of primary hepatic neuroendocrine tumor diagnosed by Al18F-NOTA-Octreotide PET/CT: a case report - Zhang, Zhongyan; Li, Hehe (Frontiers in Medicine, 2023)
Neuroendocrine tumors (NETs) are a heterogeneous group of tumors originating from peptide-producing neurons and neuroendocrine cells. The liver is the most common site of metastasis for NETs, while primary hepatic neuroendocrine tumors (PHNETs) are exceedingly rare. While somatostatin receptor scintigraphy (SRS) has demonstrated superior efficacy compared to [ 18 F]FDG PET imaging in the diagnosis of neuroendocrine tumors, [ 18 F]AlF-NOTA-Octreotide ([ 18 F]AlF-OC) PET/CT also exhibits specific advantages over SRS. This article presents a case study of a patient with a liver mass who underwent sequential [ 18 F]FDG and [ 18 F]AlF-OC PET/CT scans, ruling out hepatocellular carcinoma and confirming the diagnosis of PHNETs. Subsequently, the patient underwent surgical treatment. From another perspective, [ 18 F]AlF-OC exhibits distinct advantages.The postoperative pathology revealed a PHNETs, which further emphasizes its clinical rarity.